Uncoupled Digital Radars Creating a Coherent Sensor Network - Julian Aguilar; David Werbunat; Vinzenz Janoudi; Christina Bonfert; Christian Waldschmidt (IEEE Journal of Microwaves)
Radar networks offer the possibility to overcome the limitations of single sensors. However, without coherent signal processing, the full potential of radar networks cannot be exploited. Therefore, the synchronization of independent radar sensors is crucial in order to mitigate performance degradation due to frequency deviations of uncoupled reference oscillators. Systematically derived synchronization criteria for coupling-induced errors such as sampling frequency offset (SFO), carrier frequency offset (CFO) and symbol timing offset (STO) of uncoupled orthogonal frequency-division multiplexing (OFDM) radar sensors enable to determine hardware specifications, such as the required reference oscillator frequency stability. This aids in the design of digital radar networks and ensures error-free signal processing in advance. The concept of deriving said criteria is applicable to other modulation types used for digital radar sensors. Additionally, signal processing-based error estimation and correction methods are presented. By exploiting standard radar images, namely range profiles and range-Doppler images, the proposed methods estimate and correct any occurring SFO, CFO and STO. Furthermore, by applying the signal processing synchronization methods, they allow for a more lenient radar network design. Measurements using a 77 GHz digital radar demonstrator verify the derived criteria and error estimation and correction methods.